2006
DOI: 10.1073/pnas.0608492103
|View full text |Cite
|
Sign up to set email alerts
|

Synapse-specific regulation of AMPA receptor function by PSD-95

Abstract: PSD-95 is a major protein found in virtually all mature excitatory glutamatergic synapses in the brain. Here, we have addressed the role of PSD-95 in controlling glutamatergic synapse function by generating and characterizing a PSD-95 KO mouse. We found that the ␣-amino-3-hydroxy-5-methylisoxazole-4-propionic acid (AMPA) subtype of glutamate receptor (AMPAR)-mediated synaptic transmission was reduced in these mice. Two-photon (2P) uncaging of MNI-glutamate onto individual spines suggested that the decrease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
250
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(274 citation statements)
references
References 34 publications
(51 reference statements)
18
250
6
Order By: Relevance
“…An enhancement of LTP is also observed in PSD-95 knockout mice (Migaud et al, 1998), and similar findings were reported in another deletion mutant of PSD-95 (Beique et al, 2006). This suggests that the activity-dependent delivery of AMPARs to the synapse during LTP may occur in the absence of PSD-95, and may be mediated, for example, by Stargazin, which binds both AMPARs and PSD-95 (Schnell et al, 2002).…”
Section: Role Of Ampars In Ltpsupporting
confidence: 62%
“…An enhancement of LTP is also observed in PSD-95 knockout mice (Migaud et al, 1998), and similar findings were reported in another deletion mutant of PSD-95 (Beique et al, 2006). This suggests that the activity-dependent delivery of AMPARs to the synapse during LTP may occur in the absence of PSD-95, and may be mediated, for example, by Stargazin, which binds both AMPARs and PSD-95 (Schnell et al, 2002).…”
Section: Role Of Ampars In Ltpsupporting
confidence: 62%
“…Because of its role in long‐term potentiation (LTP), NMDAR1 is believed to strengthen synaptic plasticity, which is considered the molecular basis of learning and memory (Lau, Saha, Faris & Russek, 2004). PSD‐95 is a core component of postsynaptic density (PSD) and is thought to be important in the control of excitatory synapse function (Béïque et al., 2006; Vickers et al., 2006). Reduced expression of PSD‐95 induces cognitive and memory dysfunction (Migaud et al., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The PSD-95-like subfamily of neuronal MAGUKs (PSD-MAGUKs) includes PSD-93, SAP102, and SAP97 (15)(16)(17). Comparative studies emphasize the remarkable similarities among PSD-MAGUKs in terms of protein-protein interactions (18,19) and overlapping functions in synaptic trafficking of AMPARs at mature synapses (20)(21)(22)(23)(24). On the other hand, the temporal coincidence of the early postnatal developmental switch from NR2B-to NR2A-NMDARs with the switch from SAP102 to PSD-95 expression raises the possibility that the two processes are related (25).…”
mentioning
confidence: 99%